A Systematic Review on Inquiry-Based Writing Instruction in Tertiary Settings. (January 2023) - Lin, Vivien; Barrett, Neil E.; Liu, Gi-Zen; Chen, Howard Hao-Jan
In science disciplines, students need sufficient and well-designed support to successfully gain writing competence along the different stages of their writing development. This study examines effective inquiry-based writing pedagogies and the contextualization of scientific writing instruction for supporting student writers in the scientific community. The researchers first systematically reviewed effective pedagogical practices that can help students gain writing competence through inquiry-based learning, then explicated how scientific writing is situated in inquiry-based writing instruction (IBWI) with respect to text structures using a genre-based approach. A systematic review of 40 empirical studies published between 2000 and 2021 was conducted. The researchers examined the pedagogies, methods, and models that effectively support IBWI and identified some emerging trends that aim to raise undergraduates' scientific writing communicative competence. Implications for how scientific writing should be situated in IBWI were provided to help disciplinary faculty respond more precisely to science students' writing needs in tertiary settings.